Detector of Optical Vortices as the Main Element of the System of Data Transfer: Principles of Operation, Numerical Model, and Influence of Noise and Atmospheric Turbulence - Valerii Aksenov; Igor Izmailov; Feodor Kanev; Boris Poizner (International Journal of Optics)
The method is proposed of optical vortex topological charge detection along with a design of a corresponding detector. The developed technique is based on measurements of light field intensity. Mathematical model simulating performance of the detector is described in the paper, and results of numerical experiments are presented which illustrate recognition of a vortex in a turbulent medium and in the presence of amplitude and phase noise in the registered radiation. Influence of shifts of the system optical axis on precision of registration is also considered in the paper.